VD_FINDINFO Arrêt / 2025 / 625 vom 15. Juli 2025 - VD Tribunal cantonal (2025)
RENONCIATION À UN REVENU, REVENU HYPOTHÉTIQUE, PC, ADMISSION PARTIELLE, CALCUL | 10 LPC, 11a LPC, 4 LPC, 9 LPC, 53 al. 3 LPGA, 14a al. 2 OPC-AVS/AI